Efficient mode transition control for DM-PHEV with mechanical hysteresis based on piecewise affine H∞ strategy - Liang, Cong; Xu, Xing; Auger, Daniel J.; Wang, Feng; Wang, Shaohua (Institute of Electrical and Electronics Engineers (IEEE), 2023)
A dual motor plug-in hybrid electric vehicle (DM-PHEVs) can achieve higher power and better fuel economy through Mode Transition Process (MTP) from pure electric to hybrid driving modes. In a DM-PHEV, the MTP is more complex, with more components to be managed. As well as being a combination of a discrete stage transition and a system with continuous state evolution, the several actuators exhibit significant discontinuous dynamics and different characteristics from each other, particularly mechanical hysteresis. This makes the design of a coordinated controller challenging. In this paper, a two-layer coordinated control strategy is proposed. The upper layer is based on a stage-dependent piecewise-affine (PWA) model which is used to develop a PWA-static output feedback H ∞ strategy (PWA-SOF). The lower layer is based on a simplified actuator lag model, and a H ∞ design technique is used to develop a robust torque controller that reduces the effect of mechanical hysteresis. The resulting strategy is described as a piecewise-affine modified static output feedback (PW-MSOF) algorithm. (While the individual elements are not novel contributions to control theory, the combination and application to this problem is.) Performance indices are defined and hardware-in-the-loop (HiL) test shows that the new controller can effectively suppress the vehicle jerk without adversely affecting other aspects of system behaviour.
Keywords: Mode transition process; PWA; Mechanical hysteresis; PHEV; H∞